Piscicidal study of payhod (Albiza procera) bark extracts on nile tilapia (Oreochromis niloticus L.) fingerlings. - Encarnacion, Cielo Katrina Tabayocyoc (2010.)
The study of Payhod (Albizia procera) barks extracts for piscicidal activity against Nile tilapia (Oreochromis niloticus) was conducted by subjecting the extracts to a 48-hour static bioassay test. Sequential extraction of the crude methanolic bark extract using solvents of icnreasing polarity gave fractions that exhibited lethal activity to the test fish. The fish mortality increases as the test concentrations for all the extracts increase. The LC50 and LC100 were determiend based from the percent mortality of fish at 24-hour exposure time through the use of linear regression analysis. Out of the four extracts (methanol, n-hexane, dichloromethane and ethyl acetate), the methanol (LC50 = 2.2 ppm, LC100 = 4.5 ppm) and ethyl acetate (LC50 = 1.8ppm, LC100 = 4.5 ppm) fractions have the lowest LC values and therefore having the highest piscicidal effects. The n-hexane fraction hase the least lethal performance since it has the greatest LC50 (4.6 ppm) and LC100 (10 ppm) values. through thin layer chromatography analysis of the extracts tested, it appeared that the bioactive constituents present int he bark were polar in nature. based from the TLC results, the toxic components are likely to be saponins, alkaloids, and tannins.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Tilapia -- Fingerlings; Payhod